Separate Opinions in Lithuanian Constitutional Justice Procedure: Development and Prospects for Improvement - Valuta, Andrius (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English]The article analyses the legal regulation of separate opinions. The research is focused the procedure of constitutional justice and its legislative development. The author argues that legal regulation of separate opinions in Lithuania should be improved by assigning mandatory publication of separate opinions together (in the same form and at the same time) with judicial decisions.SummaryThe article analyses the legal regulation of separate opinions in Lithuanian administrative, civil, constitutional and criminal procedures. The research is focused on the legislative development, and its main aspects and arising problems.Separate opinion of a judge in administrative, civil and criminal procedures in Lithuania is a part of case material, not court judgement. This status deems that separate opinions produced by judges of such courts are usually undetectable by the public, unless the courts or parties of the case selectively publish them. The absence of mandatory publication makes comprehensive studies on the dissent rate in these courts impossible, and limits the knowledge of judicial decision-making in this respect.Judges of the Constitutional Court since its establishment in 1993 were banned from issuing separate opinion in an effort foster the authority of a new court, and to protect it from political influence. After long discussions, separate opinions were introduced in late 2008. However, legal regulation was and remains flawed since it allows for separate opinions to be written and published days after the public pronouncement of the Constitutional Court’s ruling. Separate opinions in this jurisdiction are also viewed as a part of case material, and not as annex to the court’s decision.It is concluded that the stated issues of the legal regulation of separate opinions should be resolved by legal amendments, which would take into account the original concept of separate opinions and comparative cases of the leading courts. Therefore, separate opinion should be mandatorily published together with court judgements (within the same form and at the same time) as their annexes, not just an addition to case material. This model would improve the quality of legal argumentation in both separate opinions and judgments, and allow for a more thorough research on judicial decision-making. It would also mitigate possibilities for political or biased interpretations of separate opinions, which arise from the possibility to write and publish separate opinions after the public pronouncement of a court judgement. concerned with environmental requirements, would satisfy the best integration of environmental protection requirements into the legal regulation of public procurement.If a narrow definition of green public procurement with significant drawbacks continues to dominate in Lithuania, there is a danger that green procurement will remain a formal instrument. It is suggested to strengthen contract enforcement and control, as well as encourage more frequent use of advanced environmental criteria, gradually moving to the exclusive implementation of these criteria.The new possibilities for the inclusion of environmental aspects into public procurement at both EU and national levels are not well implemented in the sub-legislative definition of green public procurement and its subsequent legal regulation in Lithuania. It is suggested to improve the sub-legislative regulation of green procurement accordingly by considering new environmental provisions in the public procurement regulation, implementing them in relevant environmental protection requirements.
Keywords: judicial dissent; separate opinions; constitutional court